1998
DOI: 10.1002/(sici)1520-636x(1998)10:7<682::aid-chir14>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Optically active chlorohydrins as chiral C3 and C4 building units: Microbial resolution and synthetic applications

Abstract: Production of highly optically active C3 and C4 chlorohydrins was developed by using the bacteria stereoselectively dehalogenating and assimilating the racemic substrate: Pseudomonas sp. and Alcaligenes sp. These bacteria stereoselectively assimilate (RS)‐2,3‐dichloro‐1‐propanol (DCP) and (RS)‐3‐chloro‐1,2‐propanediol (CPD) followed by microbial preparation of (R)‐ and (S)‐DCP, and (R)‐ and (S)‐CPD with >99% ee. A novel dehalogenating enzyme, halohydrin dehydro‐dehalogenase from one of the above strains, Alcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
(99 reference statements)
0
9
0
1
Order By: Relevance
“…The strain grew aerobically on many other compounds as well, including sugars, several halogenated aliphatics, and nonhalogenated alcohols. Bacterial cultures that utilize DCP and 1,3-dichloropropanol as growth substrates have been described previously, but often the substrate degradation has been incomplete due to enantioselectivity of the catabolic enzymes, which restricts the possibilities to use such organisms for bioremediation applications (8,36), whereas they may be attractive for production of optically active compounds (27,28,29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strain grew aerobically on many other compounds as well, including sugars, several halogenated aliphatics, and nonhalogenated alcohols. Bacterial cultures that utilize DCP and 1,3-dichloropropanol as growth substrates have been described previously, but often the substrate degradation has been incomplete due to enantioselectivity of the catabolic enzymes, which restricts the possibilities to use such organisms for bioremediation applications (8,36), whereas they may be attractive for production of optically active compounds (27,28,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…DS-S-7G, and this enzyme has been termed HDDase (28). The enzyme oxidatively dechlorinates (R)-3-chloro-1,2-propanediol and produces acetic acid and formic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The public first started to take notice in the mid-2000s, after large epidemiological investigations in Europe began to show transgenerational effects in humans. One study of Swedish historical records showed that men who had experienced famine before puberty were less likely to have grandsons with heart disease or diabetes than men who had plenty to eat 5 . Similar work with children in Britain reported in 2005 that fathers who had started smoking before the age of 11 had an increased risk of having boys of above average weight 6 .…”
Section: Monster Plants and Obese Childrenmentioning
confidence: 99%
“…Wholecell processes were developed by Kasai and co-workers for the production of optically active 2,3-dichloropropanol and 1-chloro-2,3-propanediol, and these compounds served as a building block for a variety of optically active compounds [7,8]. Although the enzymes that are responsible for the enantioselective degradation of halopropanols in these organisms were not characterized in much detail, it is likely that halohydrin dehalogenases play a key role, at least in 1-chloro-2,3-propanediol degradation.…”
Section: Biocatalysis With Halohydrin Dehalogenasesmentioning
confidence: 99%